(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Japan has one of the highest life-expectancy rates in the world. The traditional Japanese food and diet is primarily responsible for the good health of Japan’s population. However, the dietary patterns of the Japanese have witnessed a considerable change in recent decades. There is a shift from a traditional diet to a westernized diet that is having an adverse impact on the health and nutritional well-being of the Japanese and the food security of the nation. The present study looks at the traditional Japanese diet, especially the role of rice as the mainstay of health and nutrition. The study explains how rice plays a pivotal role in supplying the much-needed calorie suggested by the Japanese government and maintaining its overall food security levels.